Tamanho de sementes e danificação mecânica em soja no estado do Paraná - Silva, José Donizeti da (2011)
This study aimed to determine the mechanical damage in soybean seeds and the efficiency of seed grading from samples collected at sowing time in the Paraná state. For this study, it was used the method of sampling in drill box survey. The number of samples was determined for the Paraná state, for a percentage of damage in soybean seeds of 20%, that 243 samples would be sufficient to estimate with 95% of probability this parameter of seed quality. The seeds evaluations were the mechanical damage and retention of small seeds with the large ones in the classification process. The mechanical seed damage was evaluated by the method of immersion in 5% sodium hypochlorite. According to this method, it was used 100 seeds which were soaked in the solution for 10 minutes. For the analysis of the retention of small seeds in the classification process, it was used 314 samples. For this process, two replicates of 100 seeds per sample were used. Based on the results, it was obtained the following conclusions: 1 - In the process of seed classification, over than 25% of the lots had more than 10% of small seeds that remain along with the large ones; 2 - Over than 50% of the seed lots, present more than 12% of mechanical damage; 3 - There are cultivars that are less affected by mechanical damage, and 4 - Larger seeds tend to have higher mechanical damage